OPTIMASI METODE EKSTRAKSI DAN FRAKSINASI DAUN TEH HITAM, TEH PUTIH, DAN TEH HIJAU (CAMELLIA SINENSIS L.) BERDASARKAN AKTIVITAS ANTIOKSIDAN DENGAN METODE 2,2-DIFENIL-1-PIKRILHIDRAZIL (DPPH) - Amalia Haryanto, Ilmy
Camellia sinensis L. leaves extract or familiar as tea leaves have been known to have antioxidant activity. Based on processing level, tea leaves are classified into black tea, white tea, and green tea. However, there was no information regarding the optimum method of extraction and fractionation to get the highest antioxidant activity of tea leaves quantitatively. This research aimed to find an optimum method of extraction and fractionation of tea leaves based on its antioxidant activity. Tea leaves were extracted using two methods of extraction, which were maceration and fractionation. The extract which had the highest antioxidant activity was fractionated by two methods, which were liquid-liquid extraction and vacuum liquid chromatography. The optimum method was determined based on IC50 2,2-diphenyl-1- picrylhydrazyl (DPPH) reduction activity using spectrophotometer ultraviolet-visible. The highest antioxidant activity was given by maceration white tea extract with the IC50 value was 0.13 µg/mL. The levels of total flavonoids and total phenolic of black tea, white tea, and green tea leaves extract were determined to analyze the correlation between these groups of compounds with their IC50 of DPPH reduction activity. The highest levels of total flavonoid was given by maceration white tea extract which was 16.89 g QE/100 g, while the highest level of phenolic extract was given by reflux green tea extract which was 7.72 g QAE/100 g. The statistical analysis showed no correlation between total flavonoid content and total phenol with IC50 DPPH reduction activity. The highest antioxidant activity was showed by water fraction from liquid-liquid extraction with the IC50 value was 0.14 µg/mL. The optimum extraction and fractionation of tea leaves quantitatively based on its antioxidant activity were maceration and liquid-liquid extraction.